The protective effect of selenium in cisplatin-related retinotoxicity. (December 2014) - Yazici, Alper; Sogutlu-Sari, Esin; Yay, Arzu; Aksit, Hasan; Kilic, Adil; Aksit, Dilek; Yildiz, Onur; Ermis, Sitki Samet
Abstract Purpose: The aim of this study is to evaluate the retinal toxicity of cisplatin and neuroprotective effect of selenium in cisplatin-related retinal toxicity. Methods: Eighteen adult Wistar-Albino rats were divided into three groups. Group 1 (n = 6) received intraperitoneal (i.p.) injection of 2.5 ml physiologic saline for three days, group 2 (n = 6) received i.p. 16 mg/kg cisplatin for three days and group 3 (n = 6) received i.p. 16 mg/kg cisplatin for three days and 1.5 mg/kg twice daily selenium via gavage five days prior to cisplatin injection and for three days concomitantly with cisplatin injections. The total retinal thickness, outer nuclear layer (ONL), inner nuclear layer (INL) and inner plexiform layer (IPL) thicknesses were measured in hematoxylin/eosin and apoptotic index (AI) of ganglion cell layer (GCL) and INL was evaluated in TdT-mediated dUTP-biotin nick end labeling (TUNEL)-stained retina sections. Results: Selenium statistically succeeded to reduce total retinal thickness in cisplatin-toxicated retinas: from 210.17 ± 23.40 to 173.55 ± 20.43, ONL: 49.79 ± 5.32 to 41.87 ± 6.30, INL: 33.72 ± 7.93 to 25.06 ± 5.73 and IPL: 53.61 ± 8.63 to 45.61 ± 6.92 µm in hematoxylin/eosin-stained retina sections. The AI was also reduced in INL (30.10 ± 12.02 to 19.48 ± 12.99) and in GCL (37.59 ± 17.70 to 33.15 ± 13.78). However, statistical significance was present in only AI values of INL. Conclusions: Selenium limited edema due to the toxicity and reduced the retinal thickness and showed neuroprotection in cisplatin-induced retinotoxicity.